Streptococcus thermophilus ST28 Ameliorates Colitis in Mice Partially by Suppression of Inflammatory Th17 Cells. (12th October 2011) - Ogita, Tasuku; Nakashima, Megumi; Morita, Hidetoshi; Saito, Yasuo; Suzuki, Takuya; Tanabe, Soichi
Abstract : The effects of Streptococcus thermophilus ST28 on cytokine production by murine splenocytes stimulated with transforming growth factor- β plus interleukin- (IL-) 6 were evaluated. The addition of ST28 significantly repressed IL-17 production compared to ATCC 19258 (type strain). ST28 also decreased the number of Th17 cells in the stimulated splenocytes. The anti-inflammatory effects of ST28 administration were evaluated in mice with colitis induced by dextran sodium sulphate (DSS). Oral treatment of mice with ST28 ameliorated the intestinal lesions by DSS. Upon DSS treatment, IL-17 production in lamina propria lymphocytes (LPLs) was induced, but ST28 significantly decreased its production. ST28 also decreased the percentage of Th17 cells in LPL from DSS-induced colitis. The present results imply that ST28 suppresses the Th17 response in inflamed intestines and would be useful in the treatment of Th17-mediated diseases, such as inflammatory bowel disease.